18F-FDG PET/CT of Secondary Epithelioid Angiosarcoma of the Proximal Femur in a Patient With Polyostotic Fibrous Dysplasia. (October 2017) - Hakozaki, Michiyuki; Yamada, Hitoshi; Hasegawa, Osamu; Watanabe, Kazuo; Konno, Shinichi
Abstract : Abstract: Fibrous dysplasia rarely transforms into a secondary malignancy. We present the PET/CT findings at pretreatment and posttreatment in an exceedingly rare case of epithelioid angiosarcoma of the bone secondary to polyostotic fibrous dysplasia.